PERLINDUNGAN HUKUM TERHADAP BENDA CAGAR BUDAYA DI PROVINSI GORONTALO - Sutrisno Mohamad (Universitas Negeri Gorontalo, 2010)
lack of appreciation of cultural heritage obiects have been a factor increasing threats, such as theft,vandalism,and forgery of cultural heritage objects.The condition is exacerbated by the economi condition of society are minimal and weak law enforcement. for that, it should continue to be socialized that historical heritage sites and objects of cultural heritage is part of the journey of a society and nation cultural heritage sites and objects is a trail so that we can learn from the past, as well as cultural preservation is the identity of a nation, of course we do not want to lose track of the history and identity though the loss of cultural heritage objects. Keywords:legal protection,object,site,Heritage\'